2015
DOI: 10.1093/occmed/kqv149
|View full text |Cite
|
Sign up to set email alerts
|

Asthma in furniture and wood processing workers: a systematic review

Abstract: Work in this sector was associated with a significantly increased risk of respiratory symptoms and asthma. The evidence for wood dust exposure causing impaired lung function is less clearly established. Further study is required to better understand the prevalence, and causes, of respiratory problems within this sector.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 44 publications
2
22
0
Order By: Relevance
“…Workers in the furniture and wood manufacturing industry are exposed to a variety of potentially asthmagenic agents, including several types of wood dust, plicatic acid, terpenes, endotoxins, as well as formaldehyde 43 . A recent review reports a clear evidence for an association between work in wood industry and an increased risk of asthma and respiratory symptoms, in particular cough 43 . However, this association is not related to IgE sensitization in most cases.…”
Section: Other Work Environments With High Likelihood Of Irritant Expmentioning
confidence: 99%
“…Workers in the furniture and wood manufacturing industry are exposed to a variety of potentially asthmagenic agents, including several types of wood dust, plicatic acid, terpenes, endotoxins, as well as formaldehyde 43 . A recent review reports a clear evidence for an association between work in wood industry and an increased risk of asthma and respiratory symptoms, in particular cough 43 . However, this association is not related to IgE sensitization in most cases.…”
Section: Other Work Environments With High Likelihood Of Irritant Expmentioning
confidence: 99%
“…The results of this study are in a good agreement with the findings of other occupational exposure investigations. Wiggans et al [8] found that wood dust exposure resulted among workers an increased occurrence probability of dry cough (OR=1.2-5.5), cough with phlegm (OR=0.9-20), wheezing (OR=1.3-5.9), nose irritations (OR=0. 8-16.4), and eye and throat irritations (OR=1-13.5).…”
Section: Resultsmentioning
confidence: 99%
“…It has been proven that exposure to wood dust increases the risk of chronic lung disease, chronic bronchitis, nose and paranasal sinus cancer, mutagenic and genotoxic effects, eye and skin irritation, and allergic reactions. The allergic reactions, as well as occupational asthma, may be caused by bioactive compounds present in wood dust and the biological fraction (fungi and bacteria and their metabolites) [11][12][13][14][15][16][17][18][19][20][21]. The most important technical means to reduce this risk is the proper use of dust extraction systems.…”
Section: Introductionmentioning
confidence: 99%